The Degree of Availability of Teaching Competency Standards among Students of the Diploma in Educational Qualification at A'Sharqiyah University from the Point of View of the Teaching Staff (The International Journal for Scientific Research, 2024)
This research aims to measure the degree of availability of standards of teaching competencies among students of the Diploma of Educational Qualification at the Faculty of Education at A'Sharqiyah University from the point of view of the students themselves, and then provide a proposed perception to develop these competencies among students of the Diploma of Educational Qualification in the faculties of Education. The study sample consisted of students of the Diploma of Educational Qualification at A'Sharqiyah University, and the researchers used the descriptive approach (survey study) to answer the questions of this study, using the questionnaire as a tool for their study, and to verify the objectives of this research, a questionnaire was designed for the standards of teaching competencies for students of educational qualification at A'Sharqiyah University, where it included (36) teaching adequacy;  (planning, implementation and evaluation), where they were selected in a random manner.The results of the study also showed that the degree of teaching competencies for students of educational rehabilitation at the Faculty of Education at A'Sharqiyah University (research sample) in the standards of teaching competencies came to a varying degree, as the degree of availability of standards of adequacy of planning, implementation and evaluation among students of the Diploma in Education at A'Sharqiyah University came to a very large degree in the total degree, and the axes ranged between (very large, and large), where the planning axis came in the first rank, the evaluation axis came in the second rank, and the implementation axis came in the third rank. And the last. Directing leaders and education officials to pay attention to teaching competencies, provide them to teachers, and follow up on their use of them during teaching. Continue to provide training courses for teachers on professional development, increase them, follow up their results, and verify the achievement of their goals, and the researchers recommend encouraging cooperation, creativity, change, and teamwork within educational institutions.
Keywords: Teaching Competencies; Students of the Diploma in Educational Qualification; Faculty of Education; A'Sharqiyah University